1996
DOI: 10.1111/j.1365-2222.1996.tb00645.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen radical production by blood eosinophils is reduced during birch pollen season in allergic patients

Abstract: We conclude that the eosinophils of birch pollen allergic patients have reduced production of oxygen radicals when the patients are exposed to their allergen, which could depend on higher amounts of hypodense eosinophils in the blood during season.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 22 publications
2
12
1
Order By: Relevance
“…The results with a reduced oxidative metabolism after therapy with IL-2/IFN-a is reminiscent of those seen in allergic patients exposed to high doses of allergen (Woschnagg et al, 1996). The reduction may be attributed to the higher numbers of hypodense eosinophils found after IL-2/IFN-a treatment (Sedgwick et al, 1990) since hypodense eosinophils were shown to have a reduced oxidative metabolism (Woschnagg et al, 1996). The effect of the treatment may be indirect through IL-5 when eosinophils are transformed into hypodense and less active cells (Kita et al, 1992).…”
Section: Discussionmentioning
confidence: 82%
“…The results with a reduced oxidative metabolism after therapy with IL-2/IFN-a is reminiscent of those seen in allergic patients exposed to high doses of allergen (Woschnagg et al, 1996). The reduction may be attributed to the higher numbers of hypodense eosinophils found after IL-2/IFN-a treatment (Sedgwick et al, 1990) since hypodense eosinophils were shown to have a reduced oxidative metabolism (Woschnagg et al, 1996). The effect of the treatment may be indirect through IL-5 when eosinophils are transformed into hypodense and less active cells (Kita et al, 1992).…”
Section: Discussionmentioning
confidence: 82%
“…Blood was drawn from healthy individuals and eosinophils were isolated by negative magnetic immuno‐selection, as described by [16] and [17], with minor modifications [18]. Mononuclear cells were separated from red cells and granulocytes by centrifugation on 67% Percoll (Amersham Biosciences AB, Uppsala, Sweden).…”
Section: Methodsmentioning
confidence: 99%
“…Normodense and hypodense eosinophils were isolated from peri‐pheral venous blood from asymptomatic blood donors on a Percoll gradient, as previously described in detail (37).…”
Section: Methodsmentioning
confidence: 99%